Essential roles of aspartate aminotransferase 1 and vesicular glutamate transporters in β-cell glutamate signaling for incretin-induced insulin secretion. - Naoya Murao; Norihide Yokoi; Kohei Honda; Guirong Han; Tomohide Hayami; Ghupurjan Gheni; Harumi Takahashi; Kohtaro Minami; Susumu Seino (PLoS ONE, 2017)
Incretins (GLP-1 and GIP) potentiate insulin secretion through cAMP signaling in pancreatic β-cells in a glucose-dependent manner. We recently proposed a mechanistic model of incretin-induced insulin secretion (IIIS) that requires two critical processes: 1) generation of cytosolic glutamate through the malate-aspartate (MA) shuttle in glucose metabolism and 2) glutamate transport into insulin granules by cAMP signaling to promote insulin granule exocytosis. To directly prove the model, we have established and characterized CRISPR/Cas9-engineered clonal mouse β-cell lines deficient for the genes critical in these two processes: aspartate aminotransferase 1 (AST1, gene symbol Got1), a key enzyme in the MA shuttle, which generates cytosolic glutamate, and the vesicular glutamate transporters (VGLUT1, VGLUT2, and VGLUT3, gene symbol Slc17a7, Slc17a6, and Slc17a8, respectively), which participate in glutamate transport into secretory vesicles. Got1 knockout (KO) β-cell lines were defective in cytosolic glutamate production from glucose and showed impaired IIIS. Unexpectedly, different from the previous finding that global Slc17a7 KO mice exhibited impaired IIIS from pancreatic islets, β-cell specific Slc17a7 KO mice showed no significant impairment in IIIS, as assessed by pancreas perfusion experiment. Single Slc17a7 KO β-cell lines also retained IIIS, probably due to compensatory upregulation of Slc17a6. Interestingly, triple KO of Slc17a7, Slc17a6, and Slc17a8 diminished IIIS, which was rescued by exogenously introduced wild-type Slc17a7 or Slc17a6 genes. The present study provides direct evidence for the essential roles of AST1 and VGLUTs in β-cell glutamate signaling for IIIS and also shows the usefulness of the CRISPR/Cas9 system for studying β-cells by simultaneous disruption of multiple genes.